Stepwise Adaptations to Low Temperature as Revealed by Multiple Mutants of Psychrophilic α-Amylase from Antarctic Bacterium - Cipolla, Alexandre (American Society for Biochemistry and Molecular Biology, 2011)
The mutants Mut5 and Mut5CC from a psychrophilic α-amylase bear representative stabilizing interactions found in the heat-stable porcine pancreatic α-amylase but lacking in the cold-active enzyme from an Antarctic bacterium. From an evolutionary perspective, these mutants can be regarded as structural intermediates between the psychrophilic and the mesophilic enzymes. We found that these engineered interactions improve all the investigated parameters related to protein stability as follows: compactness; kinetically driven stability; thermodynamic stability; resistance toward chemical denaturation, and the kinetics of unfolding/refolding. Concomitantly to this improved stability, both mutants have lost the kinetic optimization to low temperature activity displayed by the parent psychrophilic enzyme. These results provide strong experimental support to the hypothesis assuming that the disappearance of stabilizing interactions in psychrophilic enzymes increases the amplitude of concerted motions required by catalysis and the dynamics of active site residues at low temperature, leading to a higher activity.